1988
DOI: 10.1017/s0003356100042355
|View full text |Cite
|
Sign up to set email alerts
|

The tissue and dietary protein and amino acid requirements of pigs from 8.0 to 20.0 kg live weight

Abstract: Forty-three entire males were used to determine the pig's tissue requirements for protein and amino acids from 8-0 to 20-0 kg, and provide information on the capacity of diets formulated with conventional ingredients to contain the same levels and balances of amino acids as ideal protein to supply these nutrients. Seven diets with similar digestible energy (15-9 MJ digestible energy (DE) per kg) and crude protein concentrations from 119 to 232 g/kg (8-7 to 17-3 g lysine per kg) were offered ad libitum between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
4

Year Published

1990
1990
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 18 publications
(12 reference statements)
6
21
4
Order By: Relevance
“…Bunce and King (1969) fed young rats diets widely differing in protein content and observed that the amino acid composition of whole body protein was not constant. Similar results have been reported in growing pigs using diets differing in protein (Campbell et al, 1988;Bikker et al, 1994) or amino acid contents (Batterham et al, 1990;Chung and Baker, 1992b;Gahl et al, 1996). On the other hand, Wei and Fuller (2006) found no effect of a chronic amino acid deficiency on the amino acid composition in mature rats and argued that part of the observed responses may be due to differences in growth rate and body composition, rather than to the amino acid efficiency per se.…”
supporting
confidence: 77%
“…Bunce and King (1969) fed young rats diets widely differing in protein content and observed that the amino acid composition of whole body protein was not constant. Similar results have been reported in growing pigs using diets differing in protein (Campbell et al, 1988;Bikker et al, 1994) or amino acid contents (Batterham et al, 1990;Chung and Baker, 1992b;Gahl et al, 1996). On the other hand, Wei and Fuller (2006) found no effect of a chronic amino acid deficiency on the amino acid composition in mature rats and argued that part of the observed responses may be due to differences in growth rate and body composition, rather than to the amino acid efficiency per se.…”
supporting
confidence: 77%
“…Experiments in which graded levels of lysine (Batterham et al 1990), methionine (Chung and Baker 1992a), and protein (Campbell et al 1988) were fed to pigs, lysine and methionine concentrations of carcass and whole body protein were observed to increase while glycine concentration was reported to decrease as nuffient intake increased. The range of lysine concentration of carcass protein in the current studies of 6.06-6.79 g 100 g-r protein parallels values of 6.2-6.5 [Campbell et al (1988) in whole body protein], 6.4 [Batterham et al (1990) Baker (1992a) in whole body proteinl,7.0 fKyiazakis et al (1993) in whole body proteinl, 6.86 [Krick et al (1993) in carcass proteinl, and 6.5 [Bikker et al (1994) Krick et al (1993), and Bikker et al (1994 …”
Section: Amino Acid Composition Of Carcass Proteinmentioning
confidence: 98%
“…For example, the high content of threonine in mucins (Mukkur et al 1985) may account for the low absorption of this AA in young pigs (van Goudoever et al 2000). Indeed, when these pigs were offered a low-protein milk replacer diet there was no net absorption of threonine and the apparent needs of the GIT were much higher than for lysine (405 vs. 174 µmol kg -1 h -1 ), even though body proteins have, on average, a greater molar content (+33%) for lysine (Campbell and Taverner 1988). Net losses of threonine across the GIT were also increased when the dietary protein content was raised and, in the absence of threonine oxidation , this must be due to increased endogenous losses.…”
Section: Endogenous Protein Lossesmentioning
confidence: 99%